Indeks Subjek Volume 34, Tahun 2014 - Indeks Subjek Volume 34, Tahun 2014 (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
Acceptability 285Acceptability and quality of the meat 415Acetic acid 298Active edible film 72Activated sludge 57Actuators 213Agroindustry performance 184Antagonism 430Anthocyanin 291, 374Antibacterial activity 8Antifungal 1Antimicrobial 127Antioxidant 65, 113, 127, 291, 415Antioxidant activity 399Antioxidative activity 113Arrowroot starch 14Ascorbic acid 138ASLT method 29Autoclaving-cooling cycles 146